A-Kinase Anchoring Protein 79/150 Scaffolds Transient Receptor Potential A 1 Phosphorylation and Sensitization by Metabotropic Glutamate Receptor Activation - Allison Doyle Brackley (Nature Portfolio, 2017)
Abstract Mechanical pain serves as a base clinical symptom for many of the world’s most debilitating syndromes. Ion channels expressed by peripheral sensory neurons largely contribute to mechanical hypersensitivity. Transient Receptor Potential A 1 (TRPA1) is a ligand-gated ion channel that contributes to inflammatory mechanical hypersensitivity, yet little is known as to the post-translational mechanism behind its somatosensitization. Here, we utilize biochemical, electrophysiological, and behavioral measures to demonstrate that metabotropic glutamate receptor-induced sensitization of TRPA1 nociceptors stimulates targeted modification of the receptor. Type 1 mGluR5 activation increases TRPA1 receptor agonist sensitivity in an AKA-dependent manner. As a scaffolding protein for Protein Kinases A and C (PKA and PKC, respectively), AKAP facilitates phosphorylation and sensitization of TRPA1 in ex vivo sensory neuronal preparations. Furthermore, hyperalgesic priming of mechanical hypersensitivity requires both TRPA1 and AKAP. Collectively, these results identify a novel AKAP-mediated biochemical mechanism that increases TRPA1 sensitivity in peripheral sensory neurons, and likely contributes to persistent mechanical hypersensitivity.